The Valuation of Human Capital - Weisbrod, Burton A. (Journal of Political Economy, 1961)
The market mechanism places a value on those assets to which title can be transferred, and thus the market does evaluate land and capital goods in our economy. The market also provides rental values (wage rates) for labor but not capitalized values, and these are frequently essential for rational decision-making.2I t would be useful if we could develop a substitute for the market evaluation of labor resources. This involves establishing a conceptual framework for estimating the value of assets in the form of human capital. Utilizing such a framework, quantitative estimates of capital values of people as productive assets, as a function of their sex and age, can be made. The objectives of this paper are to point up the usefulness of the concept of human-capital value, and then to develop the methods, discuss some of the difficulties, and finally to present the results of actual calculations of capitalized values of (male) human assets for the year 1950. In addition, some implications of the results for decisions on resource allocation will be considered.